Adaptación y rendimiento de grano de diez cultivares de garbanzo (Cicer arietinum L.) en Barva de Heredia (ING) - Rojas A., Marvin R.; Álvarez F., María de los Ángeles; Aguirre Rosales., Diego (Uniciencia, 1993)
A study was undertaken in Barva, Heredia, Costa Rica to evaluate the adaption and yield of ten chickpeas (Cicer arietinum L.) cultivars. Plots were planted on October 9, 1990. A complete randomized block design with four replications was used. Data was submitted to analysis of variance and analysis by using a least significant difference test. Phenological, growth and yield variables and cooking time were evaluated. The result suggest that the location were the study was conducted has good agrecological conditions for growth yield of chickpeas. Also, average cooking time was similar to a sample of chickpeas from the local market.